202k views
5 votes
Write the rational expression as an equivalent rational expression in lowest terms ((x-3)/(x²-4)). ((x²-x-6)/(x-2)).

1 Answer

5 votes

Answer:

The lowest form of the fraction is
((x-3)/(x-2) )^(2)

Explanation:

Here, the given equation is


((x-3))/((x^(2) -4)) * ((x^(2) - x - 6) )/((x-2))

Now, by ALGEBRAIC IDENTITIES, we know that:


a^(2) - b^(2)  = (a-b)(a+b)

Here,
( x^(2) -4) = (x^(2)  - (2)^(2) ) = (x-2)(x+2)

Also,
x^(2) - x -6 = (x-3)(x+2) (by splitting the middle term)

So, the given expression becomes:


((x-3))/((x^(2) -4)) * ((x^(2) - x - 6) )/((x-2)) =
((x-3))/((x-2)(x+ 2)) * ((x-3)(x+2) )/((x-2))

or, the expression becomes
((x-3))/((x-2)(x+ 2)) * ((x-3)(x+2) )/((x-2))

=
((x-3)^(2) )/((x-2)^(2) )  = ((x-3)/(x-2) )^(2)

So,the lowest form of the fraction is
((x-3)/(x-2) )^(2)

User Naasia
by
5.8k points